The influence of digital customer network strategy on hotel business - Ly, Nguyen Thi (2020)
The digital age evolution is transforming and influencing the hotel industry in various ways. The hotel industry is one of the sectors where present-day customer satisfaction impacts future business positively or negatively. In the digital age, customer feedback and reviews have moved to digital platforms leading to the formation of customer networks. Digital customer networks influence consumer perceptions, attitudes, and decisions to purchase. However, these digital customer networks are applicable as strategies to improve sales, reduce costs, and build loyal relationships with customers by maximizing access, engaging the customers, connecting, and collaborating with them. The present research slicked to assess the influence of digital customer network strategy on hotel business. For this purpose, it has been conducted an exploratory study, through interviews, in July 2020 and near five General Manager of five different hotels based in Portugal. The study shows that nowadays the digital is effectively transforming the way stakeholders do business, innovate, work and cooperate. It also adds that in future this influence will be higher, which demands an accurate attention from the management and an incorporation of digital on hotel strategies.